Duck Genetic Resources, Their Improvement And Conservation In Bangladesh: A Review - Hamid, MA (SAARC Journal of Agriculture, 2020)
The present article addresses the scenario of duck genetic resources, their production and reproduction performances, their improvement and conservation in Bangladesh. The duck, among other poultry species available in the country, are used for meat and egg production. The duck germplasm available in the country are indigenous/native, improved native, exotic and their crosses. The native duck population is comprised of Indigenous Non-descript, Deshi White, Deshi Black, Nageshwari, Sylhet Mete etc. The improved native such as, BLRI-1 and BLRI-2 are developed by Bangladesh Livestock Research Institute. The exotic duck such as, Khaki Campbell, Indian Runner, Jending, Muscovy, White Pekin, Cherry Valley, Thailand Black etc. are also used at farms level. The crossbred of different ducks are used in the country at different farming systems. Improvement and conservation of native duck are ongoing both in-situ and ex-situ in vivo by DLS, BLRI, BAU and also by others. The present study provided baseline information on duck germplasm of Bangladesh which could be useful for future genetic characterization, improvement and conservation. SAARC J. Agri., 17(2): 31-42 (2019)